Evaluation of body posture in nursing students - Marília Fernandes Andrade; Érika de Cássia Lopes Chaves; Michele Rita Oliveira Miguel; Talita Prado Simão; Denismar Alves Nogueira; Denise Hollanda Iunes (SciELO, 2017)
Abstract OBJECTIVE To investigate the body posture of nursing students before and after clinical practice. METHOD The study was developed in two stages. Initially the body posture of students of the 2nd, 4th, 6th, and 8th periods were assessed through photogrammetry. All images were analyzed in a random and masked manner with CorporisPro® 3.1.3 software. Three evaluations were performed for each angle and then the mean value was calculated. Two years later, when the 4th period students had developed their clinical internships, their body posture was again evaluated. RESULTS The total sample consisted of 112 students. Comparison of their posture with the normality pattern showed that all the angles presented significant differences (p< 0.00), except for the angle of the Thales triangle. Reassessment of these students evidenced significant differences in the angles of the acromioclavicular joint (p=0.03), knee flexion (p< 0.00) and in the tibiotarsal angle (p< 0.00). CONCLUSION All the students presented alterations when compared to the normality values. The segments that presented significant differences between before and after practice were the acromioclavicular angle, knee flexion, and tibiotarsal angle; the latter two were in the rolling position.